Accounting Students’ Perceptions of Guanxi and Their Ethical Judgments - Fan, Ying Han; Woodbine, Gordon; Scully, Glennda; Taplin, Ross (Nelison Journals, 2012)
A cross sectional study of a sample of Australian accounting students during 2011 is used to test whether the relationship concept of guanxi is accepted as a social networking concept across cultures. While favour-seeking guanxi appears to be equally important across cultural groups (as a universal set of values), its negative variant, rent-seeking guanxi continues to be sanctioned to a greater extent by students holding temporary visas from Mainland China. Contrary to the findings of Fan, Woodbine, and Scully (2012) involving Chinese auditors, this study of Australian and Chinese students did not identify favour-seeking guanxi as a factor influencing ethical judgment, whereas rent-seeking guanxi was strongly significant as a predictor of judgment making for Australian students. Major concerns are expressed about the need to sensitize Chinese students to make them more aware of unethical practices prevalent in their home country. These findings have significant implications for educators delivering ethics courses to cohorts that include international students as well as the professional bodies involved in designing development programs.